(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2025)
This article presents information about the role of consumer culture in ensuring the protection of human interests, thrift in the process of satisfying needs, the famous American economist V. Rostov, The Almighty Consumer, J. Furaste "Technology and Wellbeing